2012
DOI: 10.36076/ppj.2012/15/es59
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Chronic Pain Patients from FullOpioid Agonists to Sublingual Buprenorphine

Abstract: Background: Sublingual buprenorphine-naloxone (buprenorphine SL) is a preparation that is used to treat opioid dependence. In addition, the Drug Enforcement Administration (DEA) has acknowledged the legality of an off-label use to treat pain with a sublingual buprenorphine preparation. Buprenorphine SL is unique among the opioid class of analgesics; this compound has a high affinity for the mu-receptor, yet only partially activates it. Thus, buprenorphine SL can provide analgesia, yet minimize opioid side effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 19 publications
2
41
2
Order By: Relevance
“…35,36,47,48 Participants were rotated to buprenorphine for various indications, including inadequate analgesia with escalating opioid doses, intolerable adverse effects, and risky regimens (eg, high dose and/or coprescription with benzodiazepines). 39,40,46,47,[49][50][51][52][53] Other reasons included aberrant opioid use. [35][36][37][38]48,54,55 Opioid use disorder was present in some participants in 13 of 22 studies (59.1%), [35][36][37][38][41][42][43][44][45]47,48,52,53 whereas in 4 of 22 studies (18.2%) 27,39,40,46,[49][50][51]54,55 OUD was an exclusion criterion; however, in 2 of these studies, participants either had some aberrant opioidrelated behavior 54 or were opioid dependent by naloxone challenge.…”
Section: Study Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36,47,48 Participants were rotated to buprenorphine for various indications, including inadequate analgesia with escalating opioid doses, intolerable adverse effects, and risky regimens (eg, high dose and/or coprescription with benzodiazepines). 39,40,46,47,[49][50][51][52][53] Other reasons included aberrant opioid use. [35][36][37][38]48,54,55 Opioid use disorder was present in some participants in 13 of 22 studies (59.1%), [35][36][37][38][41][42][43][44][45]47,48,52,53 whereas in 4 of 22 studies (18.2%) 27,39,40,46,[49][50][51]54,55 OUD was an exclusion criterion; however, in 2 of these studies, participants either had some aberrant opioidrelated behavior 54 or were opioid dependent by naloxone challenge.…”
Section: Study Populationsmentioning
confidence: 99%
“…35,37,54 Individuals who were switching from methadone hydrochloride or transdermal fentanyl were instructed to wait longer (about 36-72 hours). 38,[47][48][49][50]54 In 2 protocols, participants were randomized to structured buprenorphine tapering conditions 35,56 ; in 1 study, participants were allowed to switch to the steady-dose group if they could not tolerate the tapering. 35 Another protocol required that patients were unable to taper their previous opioid use before being offered buprenorphine rotation.…”
Section: Rotation Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that buprenorphine has similar equi-analgesic properties as full mu-opioid receptor agonists, like morphine and transdermal fentanyl [26]. Studies on the effectiveness of buprenorphine rotation in patients with CNCP and OUD suggested a positive effect on pain [23,[27][28][29][30][31]. However, these studies had a small sample size [23,31], were retrospective in nature [27,28,30], or participants could self-administer additional oxycodone [29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effectiveness of buprenorphine rotation in patients with CNCP and OUD suggested a positive effect on pain [23,[27][28][29][30][31]. However, these studies had a small sample size [23,31], were retrospective in nature [27,28,30], or participants could self-administer additional oxycodone [29]. Additionally, buprenorphine has a lower risk of respiratory depression, sedation and overdose [32,33].…”
Section: Introductionmentioning
confidence: 99%